Rapid and Reversible Morphing to Enable Multifunctionality in Robots - Brittan T. Wilcox; John Joyce; Michael D. Bartlett (Advanced Intelligent Systems, 2025)
Biological organisms are extraordinary in their ability to change physical form to perform different functions. Mimicking these capabilities in engineered systems has the potential to create multifunctional robots that adapt form and function on‐demand for search and rescue, environmental monitoring, and transportation. Organisms are able to navigate such unstructured environments with the ability to rapidly change shape, move swiftly in multiple locomotion modes, and do this efficiently and reversibly without external power sources, feats which are difficult for robots. Herein, a bio‐inspired latch‐mediated, spring‐actuated (LaMSA) morphing mechanism is harnessed to near‐instantaneously and reversibly reconfigure a multifunctional robot to achieve driving and flying configurations. This shape change coupled with a combined propeller/wheel leverages the same motors and electronics for both flying and driving, providing efficiency of morphing and locomotion for completely untethered operation. The adaptive robotic vehicle can move through confined spaces and rough terrain which are difficult to pass by driving or flying alone, and expands the potential range through power savings in the driving mode. This work provides a powerful scheme for LaMSA in robots, in which controlled, small‐scale LaMSA systems can be integrated as individual components to robots of all sizes to enable new functionalities and enhance performance.